AMI galactic plane survey at 16 GHz - II. Full data release with extended coverage and improved processing - Perrott, Y.; Scaif, A.; Green, D.; Grainge, K.; Hurley-Walker, Natasha; Jin, T.; Rumsey, C.; Titterington, D. (2015)
The Arcminute Microkelvin Imager Galactic Plane Survey provides mJy-sensitivity, arcminute-resolution interferometric images of the northern Galactic plane at ≈16 GHz. The first data release covered 76° < ≈ l < ≈ 170° between latitudes of |b| < ≈ 5°; here we present a second data release, extending the coverage to 53° < ≈ l < ≈ 193° and including high-latitude extensions to cover the Taurus and California giant molecular cloud regions, and the recently discovered large supernova remnant G159.6+7.3. The total coverage is now 1777 deg2 and the catalogue contains 6509 sources. We also describe the improvements to the data processing pipeline which improves the positional and flux density accuracies of the survey.